Corporate Taxation and Dividend Behaviour–A Comment - King, M. A. (Review of Economic Studies, 1971)
Journal Article Corporate Taxation and Dividend Behaviour—A Comment Get access M. A. King M. A. King University of Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 377–380, https://doi.org/10.2307/2296390 Published: 01 July 1971